Analysis Implementation Green Tourism based Sustainable Development Goals (Case Study: Sambirejo Sub-district, Prambanan District, Sleman Regency) - Sirait, Afni; Susanto, Heri; Zuhrotun, Zuhrotun; Mulyanto, Indro Hery (Journal of Applied Business, Taxation and Economics Research, 2025)
Green tourism is a way to maintain the sustainability of the tourism world. This program was formed in line with the desire to increase the number of green jobs to achieve the Sustainable Development Goals (SDGs). This study aims to analyze the implementation of SDGs-based green tourism in Sambirejo Village. This study uses a qualitative descriptive method using questionnaires and primary data from the research object. This research was conducted from March to August 2024. The respondents in this study were the community around the tourist area in Sambirejo Village. The results of the study explain that Sambirejo Village has been trying to implement a green tourism program based on SDGs since 2019. This is evidenced by the receipt of several awards obtained for the development of environmentally based villages